The Failure Mechanism and Stability of the End Slope of Inclined Composite Coal Seam. (26th October 2021) - Li, Haoran; Du, Han; Bai, Runcai; Liu, Guangwei; Zhao, Mingyuan; Liu, Rongzheng
Abstract : In view of the inclined occurrence of coal seam in Heishan open-pit coal mine, in the longitudinal exploitation process of the first mining area, the height of the slope at the west end is increasing, and the occurrence of weak interlayer in the slope is in production. The failure mechanism and stability of the end slope of the inclined composite coal seam, which is typical of the West end slope of Heishan open-pit mine, are studied by means of field investigation, theoretical analysis, limit equilibrium analysis, and numerical simulation. The factors affecting the stability of the western side slope and the potential landslide mode are analyzed. The residual thrust method and simplified Bishop method were used to study the stability of two potential landslide modes on the western slope, and the landslide mode, final slope angle, and slope morphology were determined. FLAC 3D was used to simulate the western end of the slope, reveal its landslide mechanism, and clarify the evolution law of the slope rock mass displacement. The results show that the landslide mode at the west end of the first mining area is the combined sliding mode of "cutting and bedding." With the decrease of longitudinal mining depth, the final slope angle functions from 40° to 37°. The stress and strain are concentrated at the weak layer of the coal floor of the western side slope 13-2 and at the foot of the slope. Meanwhile, the failure also occurs inside the slope. The internal cracks connect through the weak layer of the coal floor and slide along the weak layer of the coal floor 13-2. The displacement evolution law of the slope monitoring point shows that the deformation of the slope is mainly horizontal displacement, the maximum displacement deformation is at the foot of the slope, and the degree of displacement deformation of the slope surface is obviously greater than that of the inside of the slope.